Aqueous humor levels of asymmetric dimethylarginine (ADMA) are positively associated with monocyte chemoattractant protein-1 (MCP-1) in patients with uveitis. Issue 1 (25th June 2007) - Yoshida, Y; Yamagishi, S; Ueda, S; Yoshimura, K; Okuda, S; Yamakawa, R
Abstract : Background/aims: The aim of the study was to evaluate whether aqueous humor levels of asymmetric dimethylarginine (ADMA) are associated with monocyte chemoattractant protein-1 (MCP-1). Methods: Aqueous humor levels of ADMA and MCP-1 were measured by high-performance liquid chromatography (HPLC) and ELISA, respectively, in 31 uveitis samples and nine cataract control samples. Results: Aqueous humor ADMA and MCP-1 levels were significantly higher in infectious or non-infectious uveitis patients than in controls (0.67±0.04 nmol/ml vs 0.55±0.03 nmol/ml vs 0.43±0. 04 nmol/ml (p<0.01) and 29.0±11.3 ng/ml vs 4.5±1.2 ng/ml vs 0.47±0.1 ng/ml (p<0.01), respectively). A positive correlation between ADMA and MCP-1 levels in aqueous humor was found in control and uveitis patients (r = 0.33, p<0.05). Conclusion: The results demonstrated that aqueous humor levels of ADMA were positively associated with MCP-1 in humans. Our present observations suggest that aqueous humor levels of ADMA may be a novel biomarker of inflammation in uveitis.